Current issues in fiscal policy and their implications for the conduct of monetary policy - Bank for International Settlements (Basle : Bank for International Settlements, 1992)
A meeting of central bank economists was held at the Bank for International Settlements in 1991 to discuss issues raised by recent and prospective developments in government budget deficits and, in particular, the implications for the conduct of monetary policy. This volume contains the papers presented at the meeting.
Includes bibliographical references.
ne 29/06/2018
Loans
Keywords: Fiscal policy